High Frequency Induction of Callus from Seedling Explants of Pigeonpea (Cajanus cajan [L] Millsp.) for Genetic Transformation - Ramganesh; V. Prakasam, M. Prabhakaran, S. Elumalai*, S. (Current Botany, 2011)
Pigeonpea (Cajanus cajan [L] Millsp.) is an important grain legume of the semi-arid tropics. It provides protein rich food. Seeds of Pigeonpea were collected and surface sterilized, this sterilized seeds were germinated aseptically. Various explants epicotyls (excised from 7 day old seedlings) cotyledons were used for morphogenic response. Callus induction was achieved from epicotyl and cotyledon explants of Pigeonpea. Callus induction at various frequencies were observed using different concentration and combination of IAA, kinetin and 2,4-D. Highest percentage (95) of callus formation was observed on modified MS (Murashige and Skooge) media + 1.0 mg l-1 IAA (Indole Acetic Acid) + 0.9 mg l-1 kinetin and 90 percentage of callus formation was observed on modified MS ( Murashige and Skooge) media + 1.0 mg l-1 2,4-D.